Recenzja książki Joanny Pigulak „Gra w film. Z zagadnień relacji między filmem i grami wideo”, Universitas, Kraków 2022 - Prajzner, Katarzyna (Replay. The Polish Journal of Game Studies, 2023)
What is the relationship between computer games and cinema? Why computer games tend to employ camera movement, shot-selection and framing similar to that used in the cinema? To what extent, though, is it useful to look at games more closely in the light of cinema? These are the central organising questions of Joanna Pigulak’s 2022 monograph Gra w film. Z zagadnień relacji między filmem i grami wideo. The book focuses very much on film-like quality of graphics and genres of computer games and explores the extent to which the tools of film analysis can be applied to them. The book argues persuasively that likeness between cinema and games is the reason for calling games virtual reality, what makes the main framework somewhat debatable. Pigulak’s great strength is in analysing fragments of computer games and demonstrating how differences between cinema and games are allowing for defining new qualities of interactive texts even when fundamentally similar building blocks are involved.